Roles of the RAF/MEK/ERK Pathway in Cell Growth, Malignant Transformation and Drug Resistance - McCubrey, James A.; Steelman, Linda S.; Chappell, William H.; Abrams, Stephen L.; Wong, Ellis W.T.; Chang, Fumin; Lehmann, Brian D.; Terrian, David M.; Milella, Michele; Tafuri, Agostino; Stivala, Franca; Libra, Massimo; et al. (East Carolina University, 2007)
Growth factors and mitogens use the Ras/Raf/MEK/ERK signaling cascade to transmit signals from their receptors to regulate gene expression and prevent apoptosis. Some components of these pathways are mutated or aberrantly expressed in human cancer (e.g., Ras, B-Raf). Mutations also occur at genes encoding upstream receptors (e.g., EGFR and Flt-3) and chimeric chromosomal translocations (e.g., BCR-ABL) which transmit their signals through these cascades. Even in the absence of obvious genetic mutations, this pathway has been reported to be activated in over 50% of acute myelogenous leukemia and acute lymphocytic leukemia and is also frequently activated in other cancer types (e.g., breast and prostate cancers). Importantly, this increased expression is associated with a poor prognosis. The Ras/Raf/MEK/ERK and Ras/PI3K/PTEN/Akt pathways interact with each other to regulate growth and in some cases tumorigenesis. For example, in some cells, PTEN mutation may contribute to suppression of the Raf/MEK/ERK cascade due to the ability of activated Akt to phosphorylate and inactivate different Rafs. Although both of these pathways are commonly thought to have anti-apoptotic and drug resistance effects on cells, they display different cell lineage specific effects. For example, Raf/MEK/ERK is usually associated with proliferation and drug resistance of hematopoietic cells, while activation of the Raf/MEK/ERK cascade is suppressed in some prostate cancer cell lines which have mutations at PTEN and express high levels of activated Akt. Furthermore the Ras/Raf/MEK/ERK and Ras/PI3K/PTEN/Akt pathways also interact with the p53 pathway. Some of these interactions can result in controlling the activity and subcellular localization of Bim, Bak, Bax, Puma and Noxa. Raf/MEK/ERK may promote cell cycle arrest in prostate cells and this may be regulated by p53 as restoration of wild-type p53 in p53 deficient prostate cancer cells results in their enhanced sensitivity to chemotherapeutic drugs and increased expression of Raf/MEK/ERK pathway. Thus in advanced prostate cancer, it may be advantageous to induce Raf/MEK/ERK expression to promote cell cycle arrest, while in hematopoietic cancers it may be beneficial to inhibit Raf/MEK/ERK induced proliferation and drug resistance. Thus the Raf/MEK/ERK pathway has different effects on growth, prevention of apoptosis, cell cycle arrest and induction of drug resistance in cells of various lineages which may be due to the presence of functional p53 and PTEN and the expression of lineage specific factors. Originally published Biochim Biophys Acta, Vol. 1773, No. 8, August 2007
Keywords: Raf/MEK/ERK; Signaling; Apoptosis; Drug resistance; Cancer therapy; PI3K/Akt